An equivalence study: Are patient-completed and telephone interview equivalent modes of administration for the EuroQol survey?. Issue 1 (January 2017) - Chatterji, R.; Naylor, J.; Harris, I.; Armstrong, E.; Davidson, E.; Ekmejian, R.; Descallar, J.
Abstract Background To determine if the EuroQol Health Related Quality of Life survey produces equivalent results when administered by phone interview or patient-completed forms. Methods People awaiting hip or knee arthroplasty at a major metropolitan hospital participated. They were randomly assigned to receive the EuroQol Health Related Quality of Life survey via telephone, followed by a patient completed form 1 week later, or vice versa. Equivalence was determined using two one-sided tests (TOST) based on minimal clinically-important differences for the visual analogue scale (VAS) and the summary Utility Index. Cohen's Kappa scores were computed to determine agreement for the individual EuroQoL Likert scale items. Results Seventy-six from 90 (84%) participants completed the survey twice. Based on limits set at ±7 and ±0.11 for the VAS and Utility Index, respectively, equivalence was established between the two methods of administration for both the VAS (mean difference 0.05 [90% CI −3.76–3.67]) and the Utility Index (mean difference 0.06 [90% CI 0.02–0.11]). Varying levels of agreement, ranging from slight to substantial (κ = 0.17–0.67), were demonstrated for the individual health domains. The order of telephone and patient-completed survey administration had no significant effect on results. Conclusions Equivalent results are obtained between telephone and patient-completed administration for the VAS and Utility Index of the EuroQol Survey in people with advanced hip or knee osteoarthritis. The limits of agreement for the individual health domains vary which prevents the accurate interpretation of real change in these items across modes.